2021
DOI: 10.20448/2002.131.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Bank-Tunisian SMEs Funding in a Context of Information Asymmetry

Abstract: This paper explores the determinants of access to finance for small and medium enterprises (SMEs) in the context of asymmetric information. Our sample consisted of 250 Tunisian SMEs financed by Arab International Bank of Tunisia, broken down by sector of activity, size and region. The results of multiple linear regressions showed that size, interest rate, trade credits and profitability have a significant influence on the total volume of credit. The bank considers the size of commercial and industrial SMEs, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In view of the current situation and existing problems of China's SME financing model, (Zhang & Fan, 2018) proposes a new financing model for SMEs based on cloud services under the guidance of the government, integrating multiple social resources, improving the transparency and immediacy of SME financing information and reducing the risks of investors and online platforms. Furthermore, the reputation of SMEs among their business partners plays an important role in accessing bank credit, and there is a need to adjust the behavior of banks and SMEs in order to improve their access to finance and thus improve bank-SME partnerships (Romdhane & Jebali, 2021). (Wang & Zhang, 2021) established a reputation evaluation model for SME financing risk to provide reference information for financial institutions to invest in SMEs, promoting good credit partnership between financial institutions and SMEs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In view of the current situation and existing problems of China's SME financing model, (Zhang & Fan, 2018) proposes a new financing model for SMEs based on cloud services under the guidance of the government, integrating multiple social resources, improving the transparency and immediacy of SME financing information and reducing the risks of investors and online platforms. Furthermore, the reputation of SMEs among their business partners plays an important role in accessing bank credit, and there is a need to adjust the behavior of banks and SMEs in order to improve their access to finance and thus improve bank-SME partnerships (Romdhane & Jebali, 2021). (Wang & Zhang, 2021) established a reputation evaluation model for SME financing risk to provide reference information for financial institutions to invest in SMEs, promoting good credit partnership between financial institutions and SMEs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study conducted in Algeria shows the difficulties of MSMEs in accessing financing services from the bank due to the asymmetric information problem, and the study suggests the importance of the banking industry and MSME segment to adjust their behaviours to improve the conditions and access to information; hence, improving the confidence for both parties in their financing relationship (Abdelhafid and Mohammed, 2019). Furthermore, Romdhane and Jebali (2021) explore the determinant of access to finance for MSMEs in Tunisia with regard to information asymmetry; their study concluded that the bank's financing of Tunisian small and medium-sized enterprises (SMEs) was characterised by the conditions dominated by the issues of asymmetric information. Their study further reveals the distinct treatment faced by SMEs that operate in different sectors due to the varied information asymmetry profiles.…”
Section: Mitigating Asymmetric Informationmentioning
confidence: 99%
“…Their study further reveals the distinct treatment faced by SMEs that operate in different sectors due to the varied information asymmetry profiles. In this matter, the Tunisian banks seem to consider giving loan service to SMEs that operate in the commercial-based sector, although the loan was granted with higher interest rates, and will likely dismiss the access to credit for SMEs that operates in the service-related sector because of excessive risk concern (Romdhane and Jebali, 2021). Interestingly, evidence from Italy with a more sophisticated financial system shows that SMEs with better private fundamentals are more likely to access the bond market, signifying that the SMEs with better information profiles will have greater access to alternative funding other than traditional bank financing; thus, reducing the problem of financial exclusion for this potential sector (Iannamorelli et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…W, 2015;Nahar & Sarker, 2016;Umiyati & Ana, 2017). (Romdhane & Jebali, 2021) also mentioned that location can affect the provision of credit or financing services. Thus, this study uses the variable number of branch offices to represent access to financial services.…”
Section: A Introductionmentioning
confidence: 99%